The Jewish Police in the Kaunas and Vilnius Ghettos (1941–1944) - Bubnys, Arūnas (Genocidas ir rezistencija, 2005)
The topic of the Kaunas ghetto police has been little researched in either Lithuanian historiography or the world at large. The main obstacles which prevent the research of this topic are both objective (the lack of archival sources) and subjective moral-psychological nature (the problem of collaboration of the Jewish police with the Nazis. Another problem is the need to assess the status and behaviour of various groups of ghetto inmates in a differentiated way.